Investigation on depth-dependent properties and benthic effluxes of dissolved organic matter (DOM) in pore water from plateau lake sediments. (June 2021) - Li, Shuaidong; Lu, Lingfeng; Wu, Yongfang; Zhao, Zhilong; Huang, Changchun; Huang, Tao; Yang, Hao; Ma, Xiaohua; Jiang, Quanliang
Abstract: Dissolved organic matter (DOM) in sediment pore water plays a key role in lake water quality, complexation of the contaminants, biogeochemical cycles, and even climate. To better understand the vertical dynamics and characteristics of DOM among pore water profiles, we investigated concentrations, chemical structures, and benthic fluxes of DOM in plateau lake sediments via stoichiometric analysis, ultraviolet–visible (UV–vis) absorption, three-dimensional fluorescence matrix spectroscopy (EEMs), and parallel factor model (PARAFAC). The results revealed that dissolved organic carbon (DOC), concurrent with chromophoric DOM (CDOM) and fluorescent DOM (FDOM), tended to accumulate in the anaerobic deeper layers. These trends also demonstrated a good agreement with the ammonium nitrogen (NH4 + -N) concentration, implying that the pathway of DOM dynamics was closely related to the redox state. The EEMs-PARAFAC model revealed that DOM in pore water mostly consisted of two terrestrial humic-like components (average contribution:> 60%) followed by microbial and tryptophan-like components, respectively. Terrestrial humic-like components were relatively stable, and their abundance was positively correlated with the FDOM level ( p  < 0.05). The changes of aromatic, molecular weight, and humification degree of DOM were possibly driven by microbial activities at different depths. Moreover, benthic flux estimations indicated that DOM and the total dissolved nitrogen (TDN) in inland sediments were potential sources for the overlying water and possibly affected the quality and ecological safety of lake water bodies.